Heat transfer enhancement in solar air channel with broken multiple V-type baffle. (September 2016) - Kumar, Raj; Kumar, Anil; Chauhan, Ranchan; Sethi, Muneesh
Abstract: A current investigation deals with experimental analysis of the heat transfer behavior and optimum relative width parameter of the solar air channel of aspect ratio of 10.0 with 60° angled broken multiple V-type baffles. The current experiment enclosed a wide range of parameter such as Reynolds number varied from 3000 to 8000, relative width varied from 1.0 to 6.0, relative baffle height of 0.5, relative baffle pitch of 10.0, relative discrete distance of 0.67 and relative gap width of 1.0. The obtained experimental results showed that higher overall thermal performance occurred at a relative baffle width of 5.0. Also, the results reveal that the broken multiple V-type baffles are thermo-hydraulically superior as compared to the other baffles shaped solar air channel.